Eya3 partners with PP2A to induce c-Myc stabilization and tumor progression - Lingdi Zhang (Nature Portfolio, 2018)
Eya proteins are characterised by phosphatase activity associated with both the evolutionary conserved region and the less conserved N-terminal domain (NTD). Here the authors show that NTD mediates the interaction with PP2A and regulates c-Myc phosphorylation and stability, potentially switching PP2A from a tumour suppressor to an oncogene.